9 The Statutes at Large of South Carolina: Containing the Acts Relating to Roads, Bridges and Ferries, With an Appendix, Containing the Militia Acts Prior to 1794, at 666-72 (David J. McCord ed., 1841) - (:unkn) unknown (My University, 1778)
Applied to "all male free inhabitants . . . from the age of sixteen to sixty years."391 Every militiaman had to "constantly keep in good repair, at his place of abode . . . one good musket and bayonet, or a good substantial smooth bore gun and bayonet, a cross belt and cartouch box" that could hold thirty-six rounds, "twelve rounds of good cartridges," plus "half a pound of spare powder and twenty-four spare rounds of leaden bullets or buck-shot," a cover for the gunlock, wax, worm picker, and "one screw driver or substantial knife." Instead of the musket plus bayonet, a militiaman could choose "one good rifle-gun and tomahawk or cutlass.
Keywords: MILITIAS; REQUIRED POSSESSION